Estudo sobre a viabilidade técnica da utilização de estribos verticais para o aumento da resistência à força cortante em lajes formadas por vigotas treliçadas - Costa, Paulo José Soares da (2018)
The present work carried out a theoretical-experimental study of a transverse reinforcement arrangement for slabs with lattice-reinforced joists. The objective of the research was to investigate both its structural behavior and its mechanical strength. In addition, 4 (four) models were tested in flexion to verify their resistive capacity and to compare the experimental values with the values calculated by ABNT NBR 6118 (2014), as well strength models, relative to slabs without transverse reinforcement and the truss complementary mechanism generated by the contribution of the concrete (Vc), were evaluated. It was proposed a detailing model for transverse reinforcement for lattice-reinforced joists, being compared with test models to measure their effectiveness. The theoretical analysis included the study of models used in the technical literature, like: ABNT NBR 6118 (2014), ACI-318 (2014), CSA A23.3 (2004), EFHE (2004) and Zsutty (1968). The results showed that there are significant differences for the average resistance between models, making it evident that the analyzed equations do not converge to similar values when the increase in it’s height, longitudinal reinforcement ratio or concrete compressive strength is required to obtain significant gains in shear strength. With respect to the experimental analysis, it was verified that the parameter that most influenced in the resistance to the shear strength was the transverse reinforcement ratio, maintaining the other constant parameters. Finally, the reinforcement arrangement evaluated in the experiments did not present a behavior like that with conventional stirrups and, despite the proven deficiency of the proposed detailing model, it was concluded that the use of closed stirrups in slabs with lattice-reinforced joists presented better efficiency to improve the resistance against from shear stresses.